Determinants of Profitability in Banking Sector: An Evidence from Pakistan - Raza, Hasan; Saeed, Atiya; Hena, Samreen (European Scientific Journal, ESJ, 2019)
This research explores the association of bank specific characteristics and its profitability. Profitability of bank relates to external and internal factors i.e. size, capital, loan and deposit generally. The study is mainly concerned with the internal factors which have an effect on the profitability of the banks in Pakistan. 34 Banks including 21 Local Private Banks, 9 Public Sector Commercial Banks, 4 Foreign Banks and 4 Specialized Banks operate their services in Pakistan. Data has been taken of overall banking industry from the website of the Central Bank, the State Bank Pakistan (SBP) for the period 2006-2016. Ordinary Least Square (OLS) method has been used with the help of E-View statistical software. Spread Ratio (SR) and Net Interest Margin (NIM) are considered for indicators of profitability (Dependent Variables) whereas Size, Capital, Loan and Deposit are used as explanatory variables. The result reveals that size of asset has negative and significant effects on profitability, the banks loans has positive impact on bank performance, capital associates positively with NIM but shows adverse effects on SR and Deposit does not exhibit any prominent influence on profitability of banks in Pakistan.